Sebuah Dialog Antarbudaya: Upaya Membangun Harmoni dalam Keberagaman di Lingkungan Mahasiswa PPKn: Strategi Membangun Komunikasi Efektif di Antara Mahasiswa Berbeda Budaya - Hafifatun Nuvus (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2024)
The aim of this research is to support efforts to create harmony cooperatively through intercultural dialogue in the Pancasila and Citizenship Education (PPKn) student environment. Mixed methods, also known as maxmethod, combines quantitative and qualitative research methods in one study. This study examines the factors that influence the success of intercultural dialogue, the challenges faced, and effective strategies in facilitating intercultural interactions. The research results show that communicating with people of various accents can increase understanding and tolerance between different cultural groups, although there are still challenges in overcoming prejudice and stereotypes. This study suggests that intercultural dialogue is an important effort in transforming PPKn students into agents of change who are able to create a harmonious and inclusive society.